Abortion: an infringement of the foetus' right to life in Islamic law - Alkali, Alhaji Umar; Mohd, Azizah; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina (International Islamic University Malaysia, 2015)
Under Islamic law, the life of a human being is sacred and as such, no one is allowed to kill or bring an end to the life of another except in accordance with the law. Whether a foetus under Islamic law is entitled to enjoy this protection or not is a subject that is hotly debated by Muslim scholars. Abortion has a direct link to the right to life because when abortion is done, it simply brings an end to the life of the human being in the womb that is in the process of development. Abortion is generally prohibited under Islamic law because it is tantamount to killing a human being that has not fully developed. Muslim jurists are not unanimous on the stage and conditions that can warrant the permissibility of abortion. This study therefore intends to employ a doctrinal analysis in its methodology to examine the respective views of jurists on abortion. The study examines the definition of abortion from the juristic and medical perspectives, the concept of abortion under Islamic law and authorities from the Qur’an, sunnah and scholars’ views concerning abortion, situations under which abortion may be permitted under Islamic law and the position of the law in some Muslim states. The article ends with a conclusion and recommendations on the practical steps that need to be taken in order to ensure that children’s right to life are well protected even before they are born.